Father departure and children's mental health: How does timing matter?. (February 2019) - Fitzsimons, Emla; Villadsen, Aase
Abstract: Father's permanent departure from the household in childhood has the potential to affect child mental health. The event is non-random, and a major limitation in most previous studies is lack of adequate control for unobserved confounders. Using five waves of data spanning ages 3 to 14 from the Millennium Cohort Study, a UK-wide nationally representative longitudinal study, this paper uses fixed effect models to examine the effect of paternal absence on children's mental health (i.e. externalising and internalising problems) in a sample of 6245 children. Heterogeneity of effects are examined by gender and maternal education. A novel aspect is to examine how the timing of departure matters, and to assess whether there are developmental periods that are especially sensitive to paternal departure, and whether effects are temporary or enduring. We find that paternal departure has a negative effect on child mental health, particularly on internalising symptoms. Striking gender differences emerge in examining effects by timing and duration. There are no short-term effects of departure in early childhood, and only weak evidence of females showing an increase in internalising symptoms in the medium-term. Paternal departure in later childhood, on the other hand, is associated with an increase in internalising problems in both males and females, and increased externalising symptoms for males only. We do not find maternal education to be a protective factor. Highlights: Timing of father's departure matters for children's mental health. Departure in mid-childhood more detrimental to mental health than earlier on. It increases internalising (boys and girls) and externalising (boys) problems. High maternal education not a buffer for child mental health after father departure. Departure in early childhood associated with better maternal mental health later on.